THE ROLE OF ECOLOGICAL CULTURE AS AN INDICATOR OF SUSTAINABLE DEVELOPMENT OF RELATIONS BETWEEN SOCIETY AND NATURE - Ridei, Nataliia; Rybalko, Yuliya; Kycherenko, Yuliya; Palamarchuk, Svitlana; Shofolov, Denis (European Scientific Journal, ESJ, 2014)
The paper explores pedagogical, psychological, philosophical, social, cultural and scientific sources, the approaches to modern interpretations of ecological culture and cultural ecology, also the culture of transformative processes in the relationship between society and nature is studied, subsystem of ecological culture is determined, and internal and external processes of their interaction are also exposed.